Merekonstruksi Habitat Curik Bali Leucopsar rothschildi Stresemann, 1912 di Bali Bagian Barat - Noerdjito, Mas; Roemantyo, Roemantyo; Sumampau, Tony (Perhimpunan Biologi Indonesia, 2011)
ABSTRACTHabitat Reconstruction of Bali Starling Leucopsar rothschildi Stresemann 1912 in WesternPart of Bali Island. Bali Starling Leucopsar rothschildi Stresemann 1912 is an endemic speciesof north western part of lowland of Bali Island. The land use changes of original habitat BaliStraling to resettlement and agriculture area since the year 1980, has caused this speciesmoved to the marginal habitat in the Prapatagung Peninsula and resided in Telukkelor areas. Inwet season this bird in Prapatagung Peninsula can have enough food from vegetation in themonsoon forest in Telukkelor, but in dry season the birds must look for the food in evergreenforest near Prapatagung. At the end of 2005, this species was categorized as an extinct speciesin the wild, but population in captured are still abundant. In 2007 and 2008, the release of thisbird in the nature has been done in Prapatagung peninsula area. In following year birdmonitoring showed that some pairs of these birds can breed sucessfully.The development of Bali province has caused the end of adding more the electrical powersupply from Java electrical power system. To transmite the electrical power to Bali, extra highvoltage electrical power transmission infrastructure (SUTET) that will be passing and cuttingthe lowland forest ecosystem in Prapatagung Peninsula is needed. Other infrastructures suchas JawaâBali bridge and high way were under studied to develop in similar area. Theinfrastructures were assumed will decrease the carrying capacity of evergreen forest insupporting Bali Starling food especially during dry season. Based on the recent condition,study on the habitat recovery of Bali Starling should was conducted especially on the originalhabitat that already changed. The results showed that local state land tenure of Sumberklampok,Sumberbatok, Tegalmuara and Tanjunggelap as in the past known as Bali Starling habitatshould be returned back their function as home of Bali Starling. To support this action plantinventarisation has been conducted to understand the rest of plant diversity in supportingBali Starling conservation.Key words: Bali starling, Leucopsar rothschildi, reconstruction, habitat.